PLANETARY NEBULAE IN THE INNER MILKY WAY: NEW ABUNDANCES - O. Cavichia (Revista Mexicana de Astronomía y Astrofísica, 2010)
The study of planetary nebulae in the inner-disk and bulge gives important information on the chemical abundances of elements such as He, N, O, Ar, Ne, and on the evolution of these abundances, which is associated with the evolution of intermediate-mass stars and the chemical evolution of the Galaxy. We present accurate abundances of the elements He, N, S, O, Ar, and Ne for a sample of 54 planetary nebulae located towards the bulge of the Galaxy, for 33 of which the abundances are derived here for the rst time. The abundances are obtained based on observations in the optical domain made at the National Laboratory for Astrophysics (LNA, Brazil). The data show a good agreement with other results in the literature, in the sense that the distribution of the abundances is similar to that of those works.